Negative Regulation of Cytoplasmic RNA-Mediated Antiviral Signaling - Komuro, Akihiko (2008)
The recent, rapid progress in our understanding of cytoplasmic RNA-mediated antiviral innate immune signaling was initiated by the discovery of retinoic acid-inducible gene I (RIG-I) as a sensor of viral RNA [1]. It is now widely recognized that RIG-I and related RNA helicases, melanoma differentiated-associated gene-5 (MDA5) and laboratory of genetics and physiology-2 (LGP2), can initiate and/or regulate RNA and virus -mediated type I IFN production and antiviral responses. As with other cytokine systems, production of type I IFN is a transient process, and can be hazardous to the host if unregulated, resulting in chronic cellular toxicity or inflammatory and autoimmune diseases [2-9]. In addition, the RIG-I-like receptor (RLR) system is a fundamental target for virus-encoded immune suppression, with many indirect and direct examples of interference described. In this article, we review the current understanding of endogenous negative regulation in RLR signaling and explore direct inhibition of RLR signaling by viruses as a host immune evasion strategy.